Outcomes in growth hormone-treated Noonan syndrome children: impact of PTPN11 mutation status - Alexander A L Jorge; Thomas Edouard; Mohamad Maghnie; Alberto Pietropoli; Nicky Kelepouris; Alicia Romano; Martin Zenker; Reiko Horikawa (Endocrine Connections, 2022)
Introduction: Mutations in PTPN11 are associated with Noonan syndrome (NS). Although the effectiveness of growth hormone therapy (GHT) in treating sh ort stature due to NS has been previously demonstrated, the effect of PTPN11 mutation status on the long-term outcomes of GHT remains to be elucidated. Methods: This analysis included pooled data from the observational American Norditropin Studies: Web-Enabled Research Program (NCT01009905) and the randomized, double-blinded GHLIQUID-4020 clinical trial (NCT01927861). Pediatric patients with clinically diagnosed NS and confirmed PTPN11 mutation status were eligible for inclusion. The effectiveness analysis included patients who were GHT-naïve and pre-pubertal at GHT start. Growth outcomes and safety were assessed over 4 years of GHT (Norditropin®, Novo Nordisk A/S). Results: A total of 69 patients were included in the effectiveness analy sis (71% PTPN11 positive). The proportion of females was 32.7 and 30.0% in PTPN11-positive and negative patients, respectively, and mean age at GHT start was 6.4 years in both groups. Using general population reference data, after 4 years of GHT, the mean (s.d.) height SD score (HSDS) was −1.9 (1.1) and −1.7 (0.8) for PTPN11-positive and PTPN11-negative patients, respectively, with no statistical difference observed between gr oups. The mean (s.d.) change in HSDS at 4 years was +1.3 (0.8) in PTPN11-positive patients and +1.5 (0.7) in PTPN11-negative patients (no significant differences between groups). Sa fety findings were consistent with previous analyses. Conclusions: GHT resulted in improved growth outcomes over 4 years in GHT-n aïve, pre-pubertal NS patients, irrespective of PTPN11 mutation status.